Perancangan Meme Sebagai Kampanye Untuk Remaja Tentang Bahaya Pernikahan Dini Melalui Tiktok - Adicandra, Christian; Kusumandyoko, Tri Cahyo (Universitas Negeri Surabaya, 2023)
Child marriage is a serious issue in Indonesia. Children under the age of 18 marry before they are physically and mentally ready. This has adverse effects, such as high health and social risks. The prevalence of child marriages is increasing each year, and efforts to address this issue have been lacking in terms of communication and media platforms. Therefore, a video meme campaign was designed to educate teenagers about the dangers of child marriage. This qualitative research follows the Miles and Huberman model of analysis and Robin Landa's design method. Data was collected through observation, questionnaires, literature study, and documentation. The video memes were created with an aspect ratio of 1080x1080 (1:1) using the Bebas Neue Pro sans-serif font. Three contexts were chosen: economic, psychological, and physical aspects of child marriage. The designed content was uploaded on Tiktok. Feedback from teenagers aged 15 to 20 indicates that the content effectively delivers the message and engages teenagers in understanding the issue of child marriage. Keywords: Meme, Child marriage, Video